2008
DOI: 10.1007/s11738-008-0198-7
|View full text |Cite
|
Sign up to set email alerts
|

Promotive effect of 5-aminolevulinic acid on chlorophyll, antioxidative enzymes and photosynthesis of Pakchoi (Brassica campestris ssp. chinensis var. communis Tsen et Lee)

Abstract: The objective of this article is to study the effect of 5-aminolevulinic acid (ALA) and enhanced chlorophyll content, antioxidative enzymes and photosynthesis rate by foliar application of ALA. We evaluated three concentrations (control-distilled water, T1-50 mg l -1 , T2-150 mg l -1 , T3-250 mg l -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 34 publications
7
52
0
Order By: Relevance
“…The same results have been observed in oilseed rape (Naeem et al, 2010). Previous research has also demonstrated the ability to improve g s and E of watermelon and pakchoi plants under different conditions by exogenous ALA treatment (Sun et al, 2009;Memon et al, 2009). Furthermore, Naeem et al (2011) reported that foliar spray with ALA improved relative growth rate, leaf osmotic potential, and relative water content in oilseed rape under salinity conditions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The same results have been observed in oilseed rape (Naeem et al, 2010). Previous research has also demonstrated the ability to improve g s and E of watermelon and pakchoi plants under different conditions by exogenous ALA treatment (Sun et al, 2009;Memon et al, 2009). Furthermore, Naeem et al (2011) reported that foliar spray with ALA improved relative growth rate, leaf osmotic potential, and relative water content in oilseed rape under salinity conditions.…”
Section: Discussionsupporting
confidence: 80%
“…Watanabe et al (2000) evaluated12 different PGRs and found ALA to be the most effective in improving the salt tolerance of cotton. Thus far, research conducted on ALA has mainly focused on photosynthesis (Liu et al, 2013), chlorophyll accumulation (Memon et al, 2009), the antioxidant system (Nishihara et al, 2003;Sun et al, 2009), and ion uptake (Naeem et al, 2010). Although ALA has been reported to be capable of enhancing the salt tolerance of various plants, data on the molecular mechanism of exogenous ALA application are limited.…”
Section: Introductionmentioning
confidence: 99%
“…3). A number of studies have focused on the stimulation of seedling antioxidant enzymes by ALA treatment, including: SOD in spinach seedlings subjected to salinity stress (Nishihara et al, 2003); pakchoi seedlings grown under optimal conditions (Memon et al, 2009); APX, CAT and SOD in Brassica napus under water deficit stress (Liu et al, 2011); and CAT in soybean plants from the damaging effects of cold stress (Balestrasse et al, 2010). However, the results of the present study revealed that there were no significant differences in the SOD and POD activity between the seedlings of aged rice seeds primed with ALA at various concentrations and non-primed seeds.…”
Section: Discussionmentioning
confidence: 99%
“…During measurement, the intact topmost completely expanded leaf after 50 min. The leaf temperature was adjusted to 18°C, and the relative humidity was 50%-70% (Memon et al, 2009). Each measurement was replicated for three times.…”
Section: Determination and Analysis Of Photosynthetic Parametersmentioning
confidence: 99%